Social Influences on Flood Preparedness and Mitigation Measures Adopted by People Living with Flood Risk - Donald Houston (MDPI AG, 2021)
This paper aims to analyse evidence, based on one of the largest and most representative samples of households previously flooded or living with flood risk to date, of social patterns in a range of flood resilience traits relating to preparedness prior to a flood (e.g., property adaptations, contents insurance, etc.) and mitigations enacted during and immediately following a flood (e.g., receiving a warning, evacuation into temporary accommodation, etc.). The data were collected from a 2006 survey of 1223 households from a variety of locations across Scotland between one and twelve years after major local floods. Our analysis identifies remarkably few social differences in flood preparedness and mitigation measures, although some aspects of demography, housing and length of residence in an area, as well as personal flood history, are important. In light of this finding, we argue that social differences in vulnerability and resilience to flooding arise from deep-seated socio-economic and socio-spatial inequalities that affect exposure to flood risk and ability to recover from flood impacts. The engrained, but well-meaning, assumption in flood risk management that impoverished households and communities are lacking or deficient in flood preparedness or mitigation knowledge and capabilities is somewhat pejorative and misses fundamental, yet sometimes invisible, social stratifications play out in subtle but powerful ways to affect households’ and communities’ ability to avoid and recover from floods. We argue that general poverty and inequality alleviation measures, such as tax and welfare policy and urban and community regeneration schemes, are likely to be as, if not more, important in alleviating social inequalities in the long-term impacts of floods than social targeting of flood risk management policy.